Molecular diagnosis of endemic and invasive mycoses: Advances and challenges (2014)
The diagnosis of endemic and invasive fungal disease remains challenging. Molecular techniques for identification of fungi now play a significant and growing role in clinical mycology and offer distinct advantages as they are faster, more sensitive and more specific. The aim of this mini-review is to provide an overview of the state of the art of molecular diagnosis of endemic and invasive fungal diseases, and to emphasize the challenges and current need for standardization of the different methods. The European Aspergillus PCR Initiative (EAPCRI) has made significant progress in developing a standard for Aspergillus polymerase chain reaction (PCR), but recognizes that the process will not be finished until clinical utility has been established in formal and extensive clinical trials. Similar efforts should be implemented for the diagnosis of the other mycoses in order to fully validate the current methods or reinforce the need to design new ones.This manuscript is part of the series of works presented at the 'V International Workshop: Molecular genetic approaches to the study of human pathogenic fungi' (Oaxaca, Mexico, 2012). © 2013 Revista Iberoamericana de Micología.